Core-shell structure and stability of nanocrystalline precipitates in Fe83.3Si4B8P4Cu0.7 soft magnetic amorphous alloy. (April 2023) - Lu, Chenyu; Ge, Jiacheng; Lan, Si; Wu, Xuelian; Wu, Zhenduo; Shi, Lingxiang; Wang, Anding; Zhang, Yan; Lai, Chi Long; Leung, Kit Ying; Luan, Junhua; Gilbert, Elliot Paul; et al.
Abstract: The core-shell nanostructure of α-Fe precipitates was investigated in a recently developed high-performance Fe83.3 Si4 B8 P4 Cu0.7 nanocrystalline soft magnetic alloy utilizing small-angle neutron scattering (SANS) and atom probe tomography (APT). SANS measurements under a saturating magnetic field provided evidence of core-shell structures at the nanoscale. Moreover, the core-shell structure was directly visualized from APT analysis, where P-enriched shells were found around Fe-enriched cores due to the large negative heat of mixing between Fe and P elements and the slow diffusion of P atoms. The core-shell nanostructures induced by nanoscale partitioning are effective in stabilizing the residual amorphous matrix and suppressing the crystal growth. Our findings provide insight into the microstructure of Fe-based amorphous alloys and have direct implications in alloy design for the improvement of the soft magnetic properties. Graphical abstract: Image 1 Highlights: The core-shell nanostructure was investigated by small-angle neutron scattering and atom probe tomography. The Fe-enriched core is surrounded by a prominent P-enriched shell. The formation of P-enriched shell can be attributed to the large negative heat of mixing and slow diffusion. The core-shell structures can stabilize the amorphous phase and suppress the crystal growth.